Sexual Assault-Related Interactions and Social Reactions in the Initial Months Following Assault: A Daily Diary Study - Reeves, Jonathan W. (Journal of interpersonal violence, 2025)
Most sexual assault survivors disclose to informal supporters and receive both negative and positive social reactions. Converging evidence suggests that the first months after sexual assault are a period of increased support-seeking that may be uniquely important to survivors’ recovery, especially among survivors at risk of chronic post-traumatic stress and alcohol misuse. However, no research has examined when and how often survivors talk about their assault and what social reactions they receive during this time. As such, the goal of this study was to characterize the day-to-day assault-related interactions and social reactions received by a high-risk group of survivors during the first months following sexual assault. Adult female survivors of past-10-week sexual assault with elevated assault-related post-traumatic stress and alcohol use (N = 41) completed a baseline assessment and daily diaries over 21 days as part of a larger mHealth clinical trial. Results demonstrated that assault-related interactions occurred on an average of 24.4% of days (range: 1–14 days), were more likely to occur earlier in the daily dairy period, and decreased in frequency over time. Across days, most survivors (75%) received both positive and negative reactions in these interactions, whereas fewer (20%) received only positive reactions and no one received only negative reactions. These findings suggest that survivors commonly have assault-related interactions with their supporters in the initial aftermath of the assault and that receiving both positive and negative social reactions is typical. Findings could inform future early interventions aiming to improve supporter reactions and better support survivors’ recovery.